The Innovation Imperative in Global Health: Gendered Futurity in the Sayana® Press (Medicine Anthropology Theory, 2022)
In this Position Piece, we explore the hegemony of innovation and the construction of gendered futures in global health through the Sayana® Press, a device that delivers a version of the contraceptive drug commonly known as Depo-Provera. The device has generated tremendous enthusiasm amongst global family planning advocates for its effectiveness and ease of use, including administration by community level providers and self-injection. Claims about its potential are compelling: advocates hope it will dramatically increase access to contraceptives, and thereby unlock the social and material emancipatory promise of family planning. We offer preliminary observations about Sayana Press as an ethnographic and discursive object and further the scholarly conversation on humanitarian design by considering the gendered dimensions of global health technologies. The advent of Sayana Press reflects several significant trends in global health including the intensification of the innovation imperative and the bypassing of investments in infrastructure—both bolstered by the recent rise of the ‘self-care agenda’. Further, we suggest that global health technologies are also techniques in the Foucauldian sense—scripting new subjectivities and bodily norms towards gendered futurities. Finally, we note the dual role of the state in sexual and reproductive health as both source and object of reproductive governance.